Age dynamics of somatometric indicators in composition with regards to mortality from circulatory system diseases in the population of northerners - Olga О. Alyoshina; Инесса Владиславовна Аверьянова (Siberian Journal of Life Sciences and Agriculture)
Background. Although obesity is a widely recognized risk factor for cardiovascular diseases in the ontogenetic aspect, the association of long-term changes in indices of body mass, muscle and fat tissues with the mortality from cardiovascular diseases is an open question regarding the North residents especially the population of the Magadan Region.